FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN KUNJUNGAN PASIEN ANAK BEKEBUTUHAN KHUSUS DI POLI OKUPASI TERAPI - abd gani baeda; Nita Roso Dwi Mahanani; Erwin Azizi Jayadipraja; Tasnim Tasnim (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2021)
Children with Special Needs (ABK) are children who are characterized by several degrees of disturbance in social behavior, communication, language, and various interests and activities that are narrow and repeated. This condition is caused by the effects of radiation, in the form of air pollution or radiation from chemicals contained in food or radiation due to mining activities. This study aims to analyze the factors associated with visiting compliance with children with special needs in Occupational Therapy Poly. This research is a quantitative study, with cross-sectional study design. which was carried out at the Kendari City Hospital involving 176 samples with the Chi-Square test approach. The results showed that there was a relationship between the quality of service at the Occupational Therapy Clinic with patient adherence in visits to therapy (p-value = 0.00) There was a relationship between parental motivation and patient adherence in visits to therapy (p.value = 0.00) There is an association between parental perceptions and patient adherence to therapy visits (p.value = 0.00). There was a relationship between parental knowledge and patient adherence to treatment visits (p.value = 0.00). There was a relationship between distance and patient adherence to therapy visits (p.value = 0.00). Parents are expected to be proactive in focusing occupational therapy on their children and health workers in the occupational therapy profession are expected to be able to provide health education to motivate parents.